Simulações de Monte Carlo no modelo de Ising de spins mistos com interação aleatória de campo cristalino - Gorgonho, Vinícius de Castro (2010)
The Ising model is often studied since it has exact solutions in one and two dimensions. Thus it serves as reference for further studies and applications in other areas of science, beyond physics. Despite being a simple model, it is an important tool to study phase transitions, both for fluids and for the magnetism. For models that include random fields, analytical techniques lead us only to approximate solutions. In particular, Monte Carlo simulations are a powerful tool to study these problems by providing very reliable results. In this work, we use Monte Carlo simulations to obtain the phase diagram of mixed spin (½ and 1) Ising model on square lattices, with random crystal field anisotropy. We calculated various quantities like specific heat, magnetic susceptibility and fourth-order cumulant to obtain the criticality of the system.